PENGARUH PENGAWASAN TERHADAP EFEKTIVITAS PENGGUNAAN ANGGARAN PADA KANTOR KECAMATAN KALIORANG KABUPATEN KUTAI TIMUR KALIMANTAN TIMUR - Yamani Yamani (ADMINISTRASI PUBLIK, 2019)
This study aims to determine and describe the effect of supervision on the effectiveness of budget use in the Kaliorang District Office in East Kutai Regency. Based on the results of the calculation of data analysis, the value of r count is 0.408 then compared with the price of criticism in table r Product Moment at N = 36 with a significance level of 95%, the price of criticism = 0.329. Thus it is proven: r count = 0.408> r table = 0.329 at σ = 95%, it can be concluded that there is a positive and significant influence between financial supervision on the effectiveness of financial use. So the hypothesis proposed in this study can be accepted, namely the existence of a positive and significant influence between financial supervision of the effectiveness of financial management in the Kaliorang District office in East Kutai Regency.               Based on the calculation of the coefficient of determination obtained R Square or r2 value of 25%. So it can be seen that the magnitude of the effect of supervision on the effectiveness of financial use in the Kaliorang District Office in East Kutai Regency is 25%, and 75% is influenced by other factors not measured in this study.               In general, the achievement of the OPD performance in the Kaliorang District Office of East Kutai District as of December 31, 2018 has been able to fulfill the main tasks and functions that have been charged. This can be reflected in the realization of the budget which reached 98.63%. Therefore, there are no significant obstacles in the implementation of the OPD program / activities in the Kaliorang District Office.